2005
DOI: 10.1364/opex.13.002994
|View full text |Cite
|
Sign up to set email alerts
|

Formation principles of two-dimensional compound photonic lattices by one-step holographic lithography

Abstract: From the view of crystallography, a systematic theoretical study on one-step formation of two-dimensional compound photonic lattices by four noncoplanar elliptical waves is presented. A general formula for the interference intensity of N elliptically polarized waves, and relevant phase shifts that compensate for the initial phases and control the relative position and size of the motifs, have been deduced. Using appropriate polarization configurations, four kinds of beam geometries can be used to form various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Through adjusting the parameters (such as the beam polarization, beam number and times of exposure [85,86], etc.) accurately, a variety of complex optical lattices have been achieved in experiments with holography, for example, complex lattices [87][88][89][90], quasicrystals [91][92][93][94][95], periodic quasicrystals [96], periodic complex photonic crystals constructed with a portion of photonic quasicrystals [97], Ag nanoparticles-embedded periodic and quasiperiodic microstructures [98], heterobinary and honeycomb photonic crystals [99], coupled photonic crystal resonator arrays [100] and diverse metamaterial structures [101], etc.…”
Section: Optimization Of Beam Parameters Of Holographic Methodsmentioning
confidence: 99%
“…Through adjusting the parameters (such as the beam polarization, beam number and times of exposure [85,86], etc.) accurately, a variety of complex optical lattices have been achieved in experiments with holography, for example, complex lattices [87][88][89][90], quasicrystals [91][92][93][94][95], periodic quasicrystals [96], periodic complex photonic crystals constructed with a portion of photonic quasicrystals [97], Ag nanoparticles-embedded periodic and quasiperiodic microstructures [98], heterobinary and honeycomb photonic crystals [99], coupled photonic crystal resonator arrays [100] and diverse metamaterial structures [101], etc.…”
Section: Optimization Of Beam Parameters Of Holographic Methodsmentioning
confidence: 99%
“…These four beams can generate an interference pattern which can be considered as compound photonic crystal lattices formed by combining any three beam interference [27][28][29].…”
Section: Six-fold Symmetry Roe: Nanogap Array Photonic Crystalmentioning
confidence: 99%
“…We can understand the interference pattern shifting by the procedure outlined below and introduced in reference [27]. The interference pattern can be assumed to be formed by combining the simple lattice formed without beam 1 (i.e.…”
Section: Interference Lithography By Tuning the Phase In Beammentioning
confidence: 99%
“…Trifonov et al suggested that symmetry reduction in square structures could effectively enlarge the absolute PBG [8]. Among these methods, lattice compounding is proved to be an effective and flexible method [9][10][11][12]. It is well known that no complete photonic band gap appears in the opal type square or triangular lattices which consist of rods or network of thin slabs.…”
Section: Introductionmentioning
confidence: 99%